Penentuan Secara Serempak Kadar Minor Anion (F-, Cl-, NO2-, Br-, NO3-, SO42– dan PO43-) dalam Sampel Air Botol Kemasan dengan Teknik Kromatografi Ion Kinerja Tinggi - Muhammad Amin (TECHNO: JURNAL PENELITIAN, 2020)
Analytical and separation conditions for the simultaneous determination of minor anions (F-, Cl-, NO2-, Br-, NO3-, SO42–, and PO43-) using ion chromatography technique have been optimized. In this study, ion chromatography with a suppressed conductivity detection system was applied to determine the ionic species with high sensitivity. By these conditions, it has been targeted in the determination of the seven anions in bottled drinking water samples. With concentration of 6 mM Na2CO3 and 1,2 mM NaHCO3were used as the eluent combination for all determinations. All the above anions could be completely determied and eluted were less than 30 min. All anions were displayed symmetrical peak shapes as in the chromatograms. The correlation coefficient (r) varies between 0.9995 and 1 for the above seven anions, whereas the detection limits calculated at S/N= 3 were 0.02–0.45 µg/L. The obtained optimum conditions were then applied to the simultaneous determination of minor anions in 6 bottled drinking water samples with different brands. From the overall drinking water samples which was collected commersially in North Maluku, there were no minor anions concentration exceeding the specified quality standards.